[A Brief Comparative Summary of the Criminal Law of the] United States - Robinson, Paul H (2011)
This chapter provides a very brief summary of the central features of American criminal law. Section II describes its source and current form, which is almost exclusively statutory, embodied in the criminal codes of each of the fifty American states and (to a lesser extent) the federal criminal code. Section III sketches the typical process by which a case moves through an American criminal justice system, from the report of a crime through trial and appellate review. Section IV summarizes the most basic objective and culpability requirements necessary to establish liability for an offense and the doctrines that sometimes impute those elements when they do not in fact exist. Section V describes the general defenses that may bar liability, even if the offense elements are satisfied or imputed. Finally, section VI describes the general organization of a typical American criminal code's definition of offenses and gives highlights concerning a few of the most common offenses